Follicular regulatory T cells eliminate HIV-1-infected follicular helper T cells in an IL-2 concentration dependent manner - Ollerton, Matthew T.; Folkvord, Joy M.; La Mantia, Andriana; Parry, David A.; Meditz, Amie L.; McCarter, Martin D.; D’Aquila, Richard T.; Connick, Elizabeth (Frontiers in Immunology, 2022)
Follicular helper CD4+ T cells (TFH) are highly permissive to HIV and a major foci of virus expression in both untreated and treated infection. Follicular regulatory CD4+ T cells (TFR) limit TFH numbers and function in vitro and in vivo. We evaluated the hypothesis that TFR suppress HIV replication in TFH using a well-established model of ex vivo HIV infection that employs tonsil cells from HIV uninfected individuals spinoculated with CXCR4- and CCR5-tropic HIV-GFP reporter viruses. Both CXCR4 and CCR5-tropic HIV replication were reduced in TFH cultured with TFR as compared to controls. Blocking antibodies to CD39, CTLA-4, IL-10, and TGF-beta failed to reverse suppression of HIV replication by TFR, and there were no sex differences in TFR suppressive activity. TFR reduced viability of TFH and even more so reduced HIV infected TFH cells as assessed by total and integrated HIV DNA. Exogenous IL-2 enhanced TFH viability and particularly numbers of GFP+ TFH in a concentration dependent manner. TFR reduced productively infected TFH at low and moderate IL-2 concentrations, and this was associated with decreases in extracellular IL-2. Both IL-2 expressing cells and larger numbers of FoxP3+CD4+ cells were detected in follicles and germinal centers of lymph nodes of people living with HIV. TFR may deplete TFH in vivo through restriction of IL-2 and thereby contribute to decay of the replication competent reservoir in B cell follicles during HIV infection.